Interprofessional Education for Cancer Care. (17th December 2018) - McKinlay, Eileen; White, Kristen; McChesney, Pauline; Hardie, Claire; Higgs, Rebekah; Hilder, Jo; Gallagher, Peter
Summary: Background: Cancer care is typically delivered by a range of health professionals, and is frequently a uniprofessional pre‐registration clinical placement. A workplace‐based, 6‐hour interprofessional education (IPE) pilot on cancer care, led by clinical tutors, was undertaken in a New Zealand hospital, accompanied by an external evaluation. The pilot involved a cohort of 21 dietetic, medicine, pharmacy, physiotherapy and radiation therapy students. The aim of the evaluation was to determine student and tutor reactions to IPE, and any changes in perceptions and attitudes. Methods: The evaluation used focus groups to collect data: two student groups and one tutor group. Focus groups were audio‐recorded, transcribed; the content was coded and then analysed. Results: Both students and tutors reported benefits from having IPE in the workplace environment, with cancer care seen as a suitable topic. Students reported a better understanding of professional roles, skills and the provision of collaborative care, and suggested other professions should be included in future IPE. Patient selection needed to be better tailored for physiotherapy students to ensure uniform relevance. As a result of competing demands, tutors found that they needed an 18‐month lead time to establish the IPE programme. Tutors felt that the programme had gone relatively smoothly and that they had benefitted from forming closer interpersonal relationships, but noted considerable unanticipated and unremunerated preparation time. Discussion: This short workplace‐based IPE programme elicited a positive student and tutor response, but highlighted the need for improvements: broadening the topic area, targeted patient selection, including more professions and providing administrative support for tutors. Cancer care was generally seen as a suitable topic